Creating Sustainable Tourism in Conflict-Hit Region of J&K: Post-COVID Era - Sehgal, Kartik (Digital Repository of Theses, 2024)
As a result of COVID-19, the tourism sector has been irrevocably altered in every conceivable aspect. Consequently, it has affected everyone and every business, including foreign travel, the demand for tourism, and the hotel industry. The quick spread of COVID-19 and its presence in practically every country, has compelled the authorities take unanticipated measures. The pandemic has brought critical weaknesses in global tourism, and given the present crisis, thus there is an immediate need to integrate robust solutions to alleviate the dangerous scenario's effects. Sustainable tourism is one of the ways to alleviate such concerns, although, there are several obstacles in conflict affected regions for sustainable tourism development amid the pandemic. J&K, one of India's northern states, is one of Asia's most popular tourist destinations, with Kashmir receiving exceptionally high praise. Kashmir has attained such fame despite of a continuous political disturbance and an armed conflict. Many different kinds of tourism are available in Jammu and Kashmir, including medical tourism, heritage tourism, pilgrimage tourism, and adventure tourism. Hence, there is much room for research in this domain as "How to develop sustainable tourism in a post-COVID-19 era for a conflict-affected region." Changes in tourism and travel are unavoidable after COVID-19 and are likely to be fuelled by several factors. As a result, I think it is essential to research this particular location inside the zone of active conflict to find solutions to the problems faced by the tourist sector and the business environment associated with it after COVID-19. The research approach that shall be followed and applied in this study is exploratory and descriptive, and the objective of it is to analyse the many factors surrounding tourism, sustainable tourism, tourism in conflict zones, and the influence of COVID-19 on tourism. The findings of the work will provide insights into the domain of sustainable tourism in the wake of COVID-19 and conflict for many stakeholders.